The Dynamics of Implementing E-Evaluation in Islamic Boarding Schools: A Solution-Oriented Study - Irwan Suanto; Sri Murhayati; Yuliharti Yuliharti (International Journal Labs, 2026)
Digital transformation in education has encouraged Islamic boarding schools (Pesantren) to adopt e-evaluation systems for learning assessment. However, implementing e-evaluation in Pesantren involves distinctive pedagogical, cultural, and ethical dynamics. This article examines the dynamics of e-evaluation implementation in Pesantren and proposes a contextual, value-based conceptual model for e-evaluation. The study employs a library research approach, reviewing academic books, national and international journal articles, and relevant documents on learning assessment, e-learning, and Pesantren education. Data were analyzed using content analysis to identify challenges, opportunities, and prevailing trends related to e-evaluation in Pesantren. The findings indicate that the main challenge lies in the mismatch between cognitively oriented digital assessment paradigms and the holistic educational goals of Pesantren. This article proposes an integrative conceptual model of Pesantren e-evaluation grounded in pedagogical, cultural, and ethical principles. The model positions e-evaluation as a supportive instrument for holistic assessment that reinforces educators’ roles and Islamic educational values. This study is expected to provide a conceptual reference for developing adaptive and sustainable e-evaluation systems in Pesantren during the digital era. It contributes theoretically to understanding digital transformation in traditional religious educational contexts and offers practical implications for Pesantren administrators seeking to implement adaptive evaluation systems. The research limitations include its conceptual nature, which requires empirical validation, and its focus on Indonesian Pesantren contexts, which may limit generalizability to other Islamic educational settings.